2015
DOI: 10.1051/0004-6361/201525962
|View full text |Cite
|
Sign up to set email alerts
|

Level and length of cyclic solar activity during the Maunder minimum as deduced from the active-day statistics

Abstract: Aims. The Maunder minimum (MM) of greatly reduced solar activity took place in 1645-1715, but the exact level of sunspot activity is uncertain because it is based, to a large extent, on historical generic statements of the absence of spots on the Sun. Using a conservative approach, we aim to assess the level and length of solar cycle during the MM on the basis of direct historical records by astronomers of that time. Methods. A database of the active and inactive days (days with and without recorded sunspots o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 26 publications
6
87
0
1
Order By: Relevance
“…A 22-year cycle was dominant in sunspot occurrence during the deep minimum (1645-1700), with the subdominant 11-year cycle, which became visible only in the late phase of the Maunder minimum. There is an indication that the length of solar cycle may slightly extend during and already slightly before a grand minimum (Miyahara et al 2004;Nagaya et al 2012), which is in agreement (note that the possible cycle maximum in 1650 discussed there was based on an erroneous data point and should be dismissed) with the results by Vaquero et al (2015).…”
Section: The Maunder Minimumsupporting
confidence: 77%
See 2 more Smart Citations
“…A 22-year cycle was dominant in sunspot occurrence during the deep minimum (1645-1700), with the subdominant 11-year cycle, which became visible only in the late phase of the Maunder minimum. There is an indication that the length of solar cycle may slightly extend during and already slightly before a grand minimum (Miyahara et al 2004;Nagaya et al 2012), which is in agreement (note that the possible cycle maximum in 1650 discussed there was based on an erroneous data point and should be dismissed) with the results by Vaquero et al (2015).…”
Section: The Maunder Minimumsupporting
confidence: 77%
“…Using these methods, Usoskin et al (2001b) have shown that sunspot occurrence during the Maunder minimum was gathered into two large clusters (1652-1662 and 1672-1689), with the mass centers of these clusters being in 1658 and 1679-1680. Together with the sunspot maxima before (1640) and after (1705) the deep Maunder minimum, this implies a dominant 22-year periodicity in sunspot activity throughout the Maunder minimum (Mursula et al 2001), with a subdominant 11-year cycle emerging towards the end of the Maunder minimum (Ribes and Nesme-Ribes 1993;Mendoza 1997;Usoskin et al 2000;Vaquero et al 2015) and becoming dominant again after 1700. Similar behavior of a dominant 22-year cycle and a weak subdominant Schwabe cycle during the Maunder minimum has been found in other indirect solar proxy data: auroral occurrence (Křivský and Pejml 1988;Schlamminger 1990;Silverman 1992) and 14 C data (Stuiver and Braziunas 1993;Kocharov et al 1995;Peristykh and Damon 1998;Miyahara et al 2006b).…”
Section: The Maunder Minimummentioning
confidence: 99%
See 1 more Smart Citation
“…2.3). Figure 1 also shows two recent estimates of the annual GSN by Vaquero et al (2015a), who treat generic no-sunspot records in the HS98 catalogue in a conservative way. The sunspot numbers were estimated using the activevs.…”
Section: Introductionmentioning
confidence: 99%
“…This series, however, contains a large number of generic no-spot statements (i.e. that no spots were seen on the Sun during long periods), which should be treated with caution (Kovaltsov et al 2004;Vaquero 2007;Clette et al 2014;Zolotova & Ponyavin 2015;Vaquero et al 2015a, see also Sect. 2.3).…”
Section: Introductionmentioning
confidence: 99%